Self-efficacy beliefs and their impact on the ambition of students of higher education institutions in the Sultanate of Oman from their point of view - Alharrasi, Sabra Saif Ahmed; Badzis, Mastura (Journal of Educational and Psychological Sciences, 2023)
This study aimed to explore the status of self-efficiency beliefs and their effect on the ambition of students of higher education institutions in the Sultanate of Oman. The study adopted the correlative descriptive methodology. The researcher used scale of Self-Competency Beliefs prepared by El Adl and Musawi (2020) and scale of ambition prepared by Muawwad and Abdulazim (2005). These were applied to a sample of (500) students. Sample was chosen by simple random method. Results of the study showed that the arithmetic means of the status of self-competency beliefs was (3.76). dimension of self-confidence scored the highest arithmetic means of (3.84). Dimension of perseverance to overcome obstacles ranked the second with arithmetic means of (3.83). Dimension of proactive behavior ranked the last with arithmetic means of (3.64). Arithmetic means of ambition in students was (3.93). Dimension of acceptance of the new scored the highest arithmetic means of (4.03). Dimension of frustration tolerance ranked the second with arithmetic means of (4.00). Dimension of optimism ranked the third with arithmetic means of (3.93). Dimension of goal setting ability ranked the last with arithmetic means of (3.81). Results showed that there is a considerable and direct statistically significant effect of the self-competency beliefs in the level of ambition at significance of (P ≤ 0.05). Results showed that there are no statistically significant differences between males and females in all dimensions of the scales of ambition, except for the dimension of frustration tolerance that showed statistically significant differences in favor of females. In addition, there are statically differences in the institution type in the dimension of (acceptance of the new) in favor of the government institution students, and there are no statistically significant differences for the variable of academic major. In the scale of self-competency beliefs, results showed that there are no statistically significant differences between males and females in all dimensions, except for (proactive behavior) which was in favor of males. There were no statistically significant differences in the academic major in the dimension of (proactive behavior) and dimension of (perseverance to overcome obstacles) in favor of scientific majors.
Keywords: Self-competency beliefs; level of ambition; students of higher education institutions; Sultanate of Oman